The Concept of Tajdid in Hasan Al-Banna’s Thought and Its Relevance to Contemporary Islamic Renewal - Mustafidah, Salma (Yayasan Insan Cendekia Nusantara, 2025)
Background: The concept of tajdid (Islamic renewal) is central to modern reform discourse, yet many approaches remain partial, either focusing solely on doctrinal purification or on sociocultural adaptation. Hasan al-Banna proposed an integrative model of tajdid that bridges this tension; however, systematic academic studies examining his conceptual framework remain limited. Methods: This study employs a qualitative approach using critical literature review of al-Banna’s primary works and relevant secondary sources, followed by thematic analysis to identify the principles, dimensions, and strategies of tajdid that he articulated. Key Findings: The findings reveal that al-Banna’s tajdid is integrative, comprehensive, and gradual (syāmil and tadarruj). It encompasses not only spiritual aspects but also social, educational, political, economic, and cultural domains. His model preserves the authenticity of Islamic teachings while remaining responsive to modern realities, thus avoiding both rigid scripturalism and excessive liberalization. Contribution: This study positions al-Banna as the architect of a balanced tajdid paradigm that harmonizes text and context, and it offers a conceptual framework applicable to designing reform strategies across various spheres of Muslim life. Conclusion: Hasan al-Banna’s tajdid model provides a relevant and contextual methodological foundation for the development of contemporary Islamic civilization. Nevertheless, further research is needed to examine the implementation and limitations of this model within more complex modern socio-political contexts.